A survey of race bug detection techniques for multithreaded programmes. (19th December 2014) - Hong, Shin; Kim, Moonzoo; Farchi, Eitan; Hierons, Robert M.; Lourenço, João
Summary As multithreaded programmes become popular to fully utilize multicore CPUs, many race bug detection techniques have been developed to find concurrency errors in multithreaded programmes effectively. Because these techniques have different views on target programme execution and detect race bugs of various types, it is difficult to characterize, compare and improve race bug detection techniques. This paper presents a formal execution model, which can uniformly represent various views of race bug detection techniques on target programme execution. Then, this paper classifies 43 race bug detection techniques according to their target race bugs. We classify race bugs on whether or not a bug violates operation block specification and/or data association specification. This survey provides researchers with a clear top‐down view of various race bug detection techniques. In addition, the concrete examples of various race bugs in this survey can help field engineers avoid race bugs in their multithreaded programmes. Copyright © 2014 John Wiley & Sons, Ltd.